Effect of night shift work on metabolic syndrome in adults who suffered from earthquake stress in early life - Na Li; Na Li; Na Li; Ran Wang; Ran Wang; Ran Wang; Peihua Hu; Peihua Hu; Peihua Hu; Wenting Lu; Wenting Lu; Wenting Lu; et al. (Frontiers Media S.A., 2023)
ObjectiveTo examine the role of night shift work on the risk of metabolic syndrome (MetS) in adults suffered from earthquakes prenatally or as infants and to analyse the effect of stress on factors that influence MetS in this population.MethodsWe included 870 subjects from 2014 to 2015. All subjects work as miners for the Kailuan Mining Group and were born were living in Tangshan. Participants were classified into two groups on basis of their work schedules: day shift and night shift. They were further classified into the prenatal exposure group, the infancy exposure group, and the control group based on their age during the Tangshan earthquake. This study was conducted 38 years after the earthquake. Participants' general demographic data, smoking and drinking habits, as well as work schedules were collected. All participants' sleep status was assessed with the Pittsburgh Sleep Quality Index. The measurement of all subjects' waist circumference and blood pressure was made, and triglycerides, fasting blood glucose, high-density lipoproteins, and low-density lipoproteins were measured by collecting blood samples. The definition of MetS was made after the guidelines for preventing and controlling type 2 diabetes in China (2017 Edition).ResultsA total of 187 (21.5%) workers were determined to have MetS. The incidence of MetS was greatly higher in night shift workers who were exposed to an earthquake during infancy than in day shift workers (χ2 = 8.053, p = 0.005). A multivariate logistic regression analysis displayed male participants had a higher risk develop MetS than female participants (p = 0.042, OR = 0.368, 95% CI = 0.140, 0.965). Current smokers (p = 0.030, OR = 1.520, 95%CI = 1.042, 2.218) and participants who sleep fewer than 7 h per night (p = 0.015, OR = 1.638, 95%CI = 1.101, 2.437) had a higher risk of MetS. Prenatal earthquake stress was also a risk element for MetS (p = 0.012, OR = 1.644, 95%CI = 1.115, 2.423).ConclusionThe risk of MetS is significantly higher in night shift workers exposed to earthquake stress during infancy than day shift workers. Earthquake exposure during pregnancy is an independent risk factor for MetS. Smoking and sleeping less than 7 h have a higher risk of MetS than the control group.